Effect of platelet-rich plasma on the healing of intra-bony defects treated with a natural bone mineral and a collagen membrane - Ferenc Do¨ ri (Blackwell Synergy, 2007)
Background: Regenerative periodontal therapy with a combination of platelet-rich plasma (PRP)1a natural bone mineral (NBM)1guided tissue regeneration (GTR) has been shown to result in significantly higher probing depth reductions and clinical attachment-level gains compared with treatment with open flap debridement alone. However, at present, it is unknown to what extent the use of PRP may additionally enhance the clinical outcome of the therapy compared with treatment with NBM1GTR. Aim: To clinically compare treatment of deep intra-bony defects with NBM1PRP1GTR with NBM1GTR. Material and Methods: Thirty patients suffering from advanced periodontal disease, and each of whom displayed one advanced intra-bony defect were randomly treated with a combination of either NBM1PRP1collagen membrane (GTR) or NBM1GTR. The following clinical parameters were evaluated at baseline and at 1 year after treatment: plaque index, gingival index, bleeding on probing, probing depth (PD), gingival recession and clinical attachment level (CAL). CAL changes were used as the primary outcome variable.